Literature Review : Meningkatkan Keterampilan Kepemimpinan Untuk Mencapai Tujuan Organisasi - Susan Febriantina; Amanda Rezki Ananda; Endah Sahira; Lareina Maritza; Maya Agriyani Putri (Student Scientific Creativity Journal, 2025)
This literature review explores essential leadership skills needed to achieve organizational goals, focusing on communication, decision-making, motivation, and conflict management. Effective leadership, especially in transportation, requires adapting to complex challenges, such as traffic congestion and regulatory changes, while integrating sustainable policies and technological advancements. The study highlights transformational and inclusive leadership styles as critical approaches to fostering team collaboration, trust, and innovation. Using a systematic literature review method, key trends and knowledge gaps were identified, providing a basis for future research. The findings emphasize continuous training and development programs to enhance leadership capabilities, ensuring leaders can address evolving organizational demands and drive long-term success.